Cordon phlebitis - Perdomo, Roberto; Gardiol, Valdo C (Cirugía del Uruguay, 2020)
Six cases of cordonal phlebitis following superficial inflammatory processes of the axila and thoraco-abdominal wall are reporte d. Clinical and diagnostic features are discussed, attention being drawn to the fact that it.s rareness is partly due to the lack of detention. It is a benign process often mistaken for carcinomatous lymphangitis. Pathologically it is mainly marked by an interstitial sub-acute inflamatory process giving rise to a superficial phlebitis with narrowing of the venous lumen. Thrombosis was present in one case. The important etiopathogenetic role of the infection in the available series of cases is pointed out.